Characterisation, degradation and regeneration of luminescent Ag29 clusters in solution. Issue 47 (23rd November 2016) - van der Linden, Marte; Barendregt, Arjan; van Bunningen, Arnoldus J.; Chin, Patrick T. K.; Thies-Weesie, Dominique; de Groot, Frank M. F.; Meijerink, Andries
Abstract : Bleaching of luminescent Ag29 clusters results in non-luminescent polydisperse species. Upon reduction of bleached clusters, optical properties of the cluster are recovered. Abstract : Luminescent Ag clusters are prepared with lipoic acid (LA) as the ligand. Using a combination of mass spectrometry, optical spectroscopy and analytical ultracentrifugation, the clusters are found to be highly monodisperse with mass 5.6 kDa. We assign the chemical composition [Ag29 (LA)12 ] 3− to the clusters, where LA likely binds in a bidentate fashion. The Ag29 clusters show slow degradation, retaining their deep red emission for at least 18 months if stored in the dark. Purification or exposure to light results in faster degradation. No other cluster species are observed during the degradation process. Once degraded, the clusters could easily be regenerated using NaBH4, which is not usually observed for thiolate-capped Ag clusters.